1994
DOI: 10.1016/0741-5214(94)90149-x
|View full text |Cite
|
Sign up to set email alerts
|

Consistent responses of the human vascular smooth muscle cell in culture: Implications for restenosis

Abstract: VSMC growth characteristics reflect the individual patient and are maintained in cell culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
4
19
1
1
Order By: Relevance
“…Furthermore, this consistency is also seen in cells taken from different vessels in the same patient, including those from stenotic lesions themselves. 35 By contrast, in confirmation of earlier observations, we have demonstrated that there is wide interindividual diversity in responses. 18 These findings support the assumption that differences in cellular response are reproducible and significant.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, this consistency is also seen in cells taken from different vessels in the same patient, including those from stenotic lesions themselves. 35 By contrast, in confirmation of earlier observations, we have demonstrated that there is wide interindividual diversity in responses. 18 These findings support the assumption that differences in cellular response are reproducible and significant.…”
Section: Discussionsupporting
confidence: 53%
“…It is well known that the in vitro study of SMCs, especially from human origin, is hindered by the fact that their responses vary considerably among donors. 30,31 To circumvent this, we used an immortalized cell line that we have recently developed, designated as HVTs-SM1. This cell line was developed from human vascular SMCs, stably transfected with a nonreplicative retroviral vector containing a temperature-sensitive (tsA58) mutant of the SV40 large T-antigen.…”
Section: Icam-1 Overexpression In Senescent Human Fibroblasts Is Medimentioning
confidence: 99%
“…Although the latter data were obtained in vitro and therefore subject to the potential criticism that it may not reflect the situation in vivo, the studies were performed using standard methodology which have been extensively validated in other systems. 18,19,30,31 This consideration forms the basis for such extrapolation. Theoretically, there are two potential ways by which ECs might affect SMC migration and proliferation: (1) by elaboration of specific factors affecting SMC migration and proliferation, and/or (2) by direct EC-to-SMC contact.…”
Section: Discussionmentioning
confidence: 99%